Analisis Pengaruh Variasi Parameter 3D Printing terhadap Kekuatan Tarik, Kekuatan Impak, dan Building Time menggunakan Metode Taguchi – Grey Relational Analysis - Ajeng Sukarno Putri; Bayu Wiro Karuniawan; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
The use of 3D printing in the manufacturing industry is not only limited to making prototypes, but also used in engineering applications. Optimal results in every production process are something to be achieved. One of them is a product with high tensile strength and impact strength, and fast building time. This study discusses the optimization of 3D printing results which are used as reference materials in the development of 3D printing technology. The experimental design used in this study was the Taguchi method with the orthogonal matrix L9(34) with three replications. The optimal combination of combined response is obtained by using the Gray Relational Analysis approach. Furthermore, a confirmation experiment was carried out as a validation of the experiment’s success. The optimal parameter results are layer height of 0.3 mm, infill pattern with a concentric pattern, and print speed of 60 mm/s. Based on the combined response analysis, the layer height parameter contribution is 51.576%, the infill pattern is 32.021%, and the print speed is 6.574%.